Efectiveness of Gyrinops Versteegii Leaves Extraction Based on Maceration Method - Putri, Yayan Suherna; Wangiyana, I Gde Adi Suryawan; Nahlunnisa, Hafizah (Jurnal Silva Samalas, 2021)
G. versteegii leaves is a raw material of agarwood tea product that needs to be further analyzed by extraction method. The aim of this research is to examine the effectiveness of G. versteegii leaves extraction based on the maceration method. G. versteegii’s leaves were taken from Duman Village West Lombok. Nusa Tenggara Barat. This research used a Completely Randomized Design with factorial arrangement of two treatment factors investigated under 3 replications each as follows: leaves processing (P1=fresh leaves, P2= dried leaves) and extraction solvent (S1=ethanol, S2= ethyl acetate, S3=Aquadest). Crude extract weight data were analyzed using ANOVA and DMRT at 5% level of significance. The result has shown that Main factors and interaction factors were significantly affected crude extract weight. Dried leaves have a higher crude extract weight than fresh leaves. Ethanol has the highest crude extract weight among others extraction solvents. There was a positive relation of interaction factor between leaves processing and extraction solvent. It could be concluded that leaves drying and ethanol solvent are the treatments that could support the effective extraction method of G. versteegii leaves based on the maceration method.